Worldwide Shifts in Mission from 1910 to 2010: A Sketch - Wild-Wood, Emma ca. 20./21. Jh. (Theology, 2010)
2010 is the centenary of the influential Edinburgh World Missionary Conference. To mark the centenary, mission scholars and practitioners across the world are engaged in processes of reflection on contemporary challenges of mission. This article briefly examines the 1910 Conference and outlines some changes in the understanding and context of mission over the century, emphasizing the spread of the Christian Church across the globe since 1910. It concludes by describing the studies of mission and world Christianity and their influence on the 2010 study process.